Qualitative and quantitative change in political participation in Kazakhstan: between ‘civic’ and ‘political’, ‘rational’ and 'post-materialist’ conventional and unconventional modes (Journal of Philosophy Culture and Political Science, 2024)
The level of political engagement and participation is commonly taken as an element of a sustainable and developed nation. The authors claim that for Kazakhstan to build conditions fostering its successful progressive development is the task of vital importance. Thus, the goal of the article is to establish how well the social and political developments in Kazakhstan regarding political engagement and participation coincide with the development in the theoretical realm. The article consists of the literature review followed by the discussion of the cases illustrating the theoretical claims in the literature that is, in turn, reinforced by the primary qualitative and quantitative data collected by the authors during the research project they have recently concluded.The authors argue that Kazakhstan’s case is a clear confirmation of the tendencies observed by the empirical researchers and delt with by the theoretical scholars, namely that political and civic engagement and participation are increasingly difficult to distinguish, that the forms and means thereof increase quantitatively and qualitatively, and that so did ‘post-materialist’ motivation behind such participation. Finally, the authors note that not only the focus of research shifts from ‘rational choice’ and ‘resource mobilization’ perspective to a more ‘post-materialist’ ‘identity’ paradigm, but that the recent patterns in political engagement and participation in Kazakhstan demonstrate the validity of such argumentation.Key words: political engagement, conventional political participation, unconventional political participation, forms and dynamics of political participation, political communication.